2015
DOI: 10.1681/asn.2015050523
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Reconstitution after Rituximab Treatment in Idiopathic Nephrotic Syndrome

Abstract: The pathogenesis of nephrotic syndrome is unclear. However, the efficacy of rituximab, a B cell-depleting antibody, in nephrotic syndrome suggests a pathogenic role of B cells. In this retrospective study, we determined by flow cytometry levels of B and T cell subpopulations before and after rituximab infusion in 28 pediatric patients with frequently relapsing or steroid-dependent nephrotic syndrome. At baseline, patients had lower median percentages of transitional and mature B cells than age-matched healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
165
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(182 citation statements)
references
References 50 publications
13
165
0
2
Order By: Relevance
“…A recent study of 28 pediatric patients with frequently relapsing steroid-sensitive nephrotic syndrome showed that delayed reconstitution of switched memory B cells after rituximab treatment was protective against relapse (25). In contrast, the 22 patients in our study represented a difficult spectrum of nephrotic syndrome, where rituximab was indicated because of treatment refractoriness or CNI toxicity with evidence of increasing glomerulosclerosis on repeat renal biopsy.…”
Section: Discussionmentioning
confidence: 54%
“…A recent study of 28 pediatric patients with frequently relapsing steroid-sensitive nephrotic syndrome showed that delayed reconstitution of switched memory B cells after rituximab treatment was protective against relapse (25). In contrast, the 22 patients in our study represented a difficult spectrum of nephrotic syndrome, where rituximab was indicated because of treatment refractoriness or CNI toxicity with evidence of increasing glomerulosclerosis on repeat renal biopsy.…”
Section: Discussionmentioning
confidence: 54%
“…Though its overall safety profile is reassuring (56), rituximab use in children is not without rare serious side effects: fulminant myocarditis, pulmonary fibrosis, fatal Pneumocystis jirovecii infections, severe ulcerative colitis, and severe allergic reactions (reviewed in Avner et al [11]). We have shown that, in children with frequently relapsing NS or steroid-dependent NS, rituximab infusion determines a prolonged depletion of memory B cells (33), and have observed long-term hypogammaglobulinemia in a few patients. Therefore, prospective long-term studies are necessary to evaluate the effect of repeated infusions on immune competence in the pediatric setting.…”
Section: Nonsteroidal Immunosuppressive Drugsmentioning
confidence: 93%
“…Moreover, after rituximab infusion, some patients maintain prolonged remission despite reconstitution of B cells (32). Regarding this aspect, we have recently shown that after rituximab-induced B cell depletion in children with frequently relapsing nephrotic syndrome or steroid-dependent nephrotic syndrome, the reconstitution of memory B cells predicts relapse (33). Targeting B cells may affect costimulatory pathways involved in T cell activation, and this may well be one of the mechanisms involved in the effectiveness of CD20-depleting agents, such as rituximab and the newer humanized anti-CD20 monoclonal antibody, ofatumumab (34).…”
Section: Pathogenesismentioning
confidence: 99%
“…Clinically, it has been shown that there is no clear relationship between the duration of the response to rituximab and the timing of recovery of B cells. It is this gap in knowledge that Colucci et al 10 address in their important paper in this issue of the Journal of the American Society of Nephrology. Colucci et al 10 studied 28 children with presumed MCD on the basis of a history of frequently relapsing or steroid-dependent disease.…”
mentioning
confidence: 98%
“…It is this gap in knowledge that Colucci et al 10 address in their important paper in this issue of the Journal of the American Society of Nephrology. Colucci et al 10 studied 28 children with presumed MCD on the basis of a history of frequently relapsing or steroid-dependent disease. In line with standard clinical practice in pediatric nephrology, the diagnosis of MCD was made on the basis of responsiveness to steroids and not on the basis of a kidney biopsy.…”
mentioning
confidence: 98%